Answer:
See below
Step-by-step explanation:
Do you mean -12(x+5)=-10?
Divide both sides by -12 -> x+5=10/12
Subtract 5 on both sides -> x=10/12-5 -> x=-4 1/6
So x=-4 1/6
Let me know if this wasn't the right equation
Answer:
A third of 9 is 3.
Step-by-step explanation:
9 / 3 = 3.
3 * 3 = 9
Answer:
0.09
0.16
0.35
0.65
0.19
0.56
Step-by-step explanation:
The solution to the quadratic equation 2x² - 4x - 3 = 0 is x = 1 ± √2.5
<h3>What is an
equation?</h3>
An equation is an expression that shows the relationship between two or more numbers and variables.
Solving the polynomial using completing the square:
2x² - 4x - 3 = 0
First divide through by 2:
x² - 2x - 3/2 = 0
add 3/2 to both sides:
x² - 2x - 3/2 + 3/2 = 0 + 3/2
x² - 2x = 3/2
add the square of half the coefficient x to both sides:
x² - 2x + 1 = 3/2 + 1
(x - 1)² = 2.5
taking square root:
x - 1 = ±√2.5
x = 1 ± √2.5
The solution to the quadratic equation 2x² - 4x - 3 = 0 is x = 1 ± √2.5
Find out more on equation at: brainly.com/question/2972832
#SPJ1